Combined Ultrasound Guided Infiltration of The Posterior Capsule of The Knee (IPACK) With Adductor Canal Block Versus Adductor Canal Block Alone in Knee Arthroscopy - Hend Mostafa Abosaifa*, Nashwa Mohammed Ibrahiem, Gihan Eissa Zahran, Hend Abdelmonem Elsakhawy, Wafaa Ali Abd Elhadi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: The optimal approach to managing pain after reconstruction of anterior cruciate ligament (ACL) remains uncertain. This research aimed to assess the effectiveness and safety of using the IPACK block as an adjunct to adductor canal block for pain relief in cases had reconstruction of ACL.